OP0245 MICROBIOTA-INDUCED INTESTINAL BARRIER DYSFUNCTION PRECEDES THE ONSET OF ARTHRITIS AND ALLOWS THE SHUTTLING OF IMMUNE CELLS FROM THE GUT THE JOINTS. (2nd June 2020) - Zaiss, M.; Taijc, N.; Sarter, K.; Azizov, V.; Bucci, L.; Luo, Y.; Cañete, J. D. D.; Ciccia, F.; Schett, G.
Abstract : Background: While it is known that microbial dysbiosis is associated with the onset of rheumatoid arthritis, mechanistic insights how it facilitates the development of arthritis remained largely elusive to date. It is especially interesting how microbial dysbiosis affects the transition from asymptomatic autoimmunity to arthritis. We speculated that a breakdown of intestinal barrier function caused by microbial dysbiosis allows immune cells to shuttle from the gut to the joints. Objectives: To test whether intestinal barrier function is impaired before the onset of human RA and experimental arthritis and to seek for evidence that immune cells from the gut migrate to the joints. Methods: In a longitudinal cohort of RA-at risk individuals markers of disturbed intestinal barrier function, such as zonulin, were analysed and linked to RA onset. Furthermore, new-onset RA patients were assessed for gut leakiness and their intestinal biopsies for the expression of tight junction proteins and immune cell infiltration. In the murine model of collagen-induced arthritis, sequential analysis of intestinal dysbiosis, intestinal barrier function and arthritis onset was carried out. Additionally, barrier function was assessed on intestinal organoids exposed to faecal supernatants from eu- and dysbiotic mice with and without inhibition of zonulin. Furthermore, three types of interventions restoring intestinal barrier function were carried out for testing their effects on the inhibition of arthritis onset. Finally, photo- converted cells from the gut were traced in the joints to test for cellular trafficking from one to the other compartment. Results: Zonulin, a potent regulator for intestinal tight junctions, was elevated in autoimmune mice and men before the onset of arthritis and predicted the onset of human RA. Intestinal barrier functions as well as epithelial tight junctions were decreased before the onset of experimental arthritis and at onset of human RA. In mice, induction of autoimmunity was followed by rapid intestinal dysbiosis followed by gut leakiness before arthritis started. Faecal supernatants of arthritic mice induce epithelial barrier dysfunction in intestinal organoids in zonulin dependent manner. Restoration of the intestinal barrier in the pre-phase of arthritis using butyrate, CB1R agonist or zonulin antagonist larazotide inhibited the development of arthritis. Finally, using photoconvertible mice, gut-borne immune cells were identified that homed to the joints when barrier function was impaired. Conclusion: In summary, these data show the intestinal barrier dysfunction precedes the onset of RA and allows the trafficking of immune cells from the gut to the joints. Targeting of intestinal tight junction function may therefore allow preventing the onset of RA. Acknowledgments: Funded by the DFG-FOR2886 PANDORA, DFG–CRC118, Staedtler foundation, Johannes und Frieda Marohn-Stiftung, Else Kröner-Fresenius foundation, Interdisciplinary Centre for Clinical Research, Erlangen (IZKF), BMBF-MASCARA and the IMI funded projectRTCure. Disclosure of Interests: Mario Zaiss: None declared, Narges Taijc: None declared, Kerstin Sarter: None declared, Vugar Azizov: None declared, laura Bucci: None declared, Yubin Luo: None declared, Juan de Dios Cañete: None declared, francesco ciccia Grant/research support from: pfizer, novartis, roche, Consultant of: pfizer, novartis, lilly, abbvie, Speakers bureau: pfizer, novartis, lilly, abbvie, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB